The effect of employee placement, work motivation and work environment on employee performance with job satisfaction as an intervening variable - Ros Hayati Rosna; Philipus Tule; Simon Sia Niha; Henny A. Manafe (Institute of Computer Science (IOCS), 2023)
At the Higher Education Service Institution Region XV Kupang, the purpose of this study was to determine and evaluate the employee performance and the function of job satisfaction as an intervening variable among the factors that influence it. The sampling technique consisted of a census of 57 Higher Education Service Institution Region XV Kupang employee respondents. This form of research falls under the category of Quantitative research, uses primary and secondary data, and employs descriptive statistical analysis and inferential statistical analysis for data analysis. The results of inferential statistical testing indicate that Employee Placement, Work Motivation, and Work Environment have a significant effect on employee Job Satisfaction; that employee Job Satisfaction has a significant effect on employee performance; and that employee Job Satisfaction mediates the effect of Employee Placement, Work Motivation, and Work Environment on employee performance at the Higher Education Service Institution Region XV Kupang.Employee Job Satisfaction is influenced by variables other than Employee Placement, Work Motivation, and Work Environment to the extent of 88.1%. Employee Placement, Work Motivation, Work Environment, and Job Satisfaction influence Employee Performance by 93.8%, while the remaining 6.2% is influenced by variables not included in this model.